Technical Review on Endoscopic Treatment Devices for Management of Upper Gastrointestinal Postsurgical Leaks - Renato Medas; Eduardo Rodrigues-Pinto (Gastroenterology Research and Practice)
Upper gastrointestinal postsurgical leaks are challenging to manage and often require radiological, endoscopic, or surgical intervention. Nowadays, endoscopy is considered the first-line approach for their management, however, there is no definite consensus on the most appropriate therapeutic approach. There is a wide diversity of endoscopic options, from close-cover-divert approaches to active or passive internal drainage approaches. Theoretically, all these options can be used alone or with a multimodality approach, as each of them has different mechanisms of action. The approach to postsurgical leaks should always be tailored to each patient, taking into account the several variables that may influence the final outcome. In this review, we discuss the important developments in endoscopic devices for the treatment of postsurgical leaks. Our discussion specifically focuses on principles and mechanism of action, advantages and disadvantages of each technique, indications, clinical success, and adverse events. An algorithm for endoscopic approach is proposed.